4-Sulphamoylphenyl semicarbazones with anticonvulsant activity - Yogeeswari P.; Sriram D.; N.pandeya S.; Stables J.P. (My University, 2025)
A series of 4-sulphamoylphenyl semicarbazone derivatives were prepared starting from sulphanilamide and screened for anticonvulsant activity. The results indicated that greater protection was obtained in the maximal electroshock screen (MES) and subcutaneous strychnine (scSTY) than the subcutaneous pentylenetetrazole (scPTZ) tests. All the compounds showed low neurotoxicity when compared to the clinically used drugs. Compounds with substituted acetophenone (8-11) showed good activity in the rat oral MES screen. Seven compounds (6, 8-10, 12, 14 and 15) exhibited anticonvulsant activity greater than sodium valproate. Among the new derivatives evaluated, compound 10 emerged as the most active compound as indicated by its protection in the MES and scSTY screens and with low neurotoxicity. Seven compounds possessed sedative-hypnotic activity. © 2004 Elsevier SAS. All rights reserved.